“Uncover” The Influence of Islamic Work Ethics on Employees’ Organizational Commitment - Arman Hj. Ahmad; Sharifah Nur Syakirah Syed Hilal; Ridzuan Masri; Azizan Mohamed Isa; Nur Syairah Ani; Wan Sabri Wan Hussin (International Journal of Economics, Business and Innovation Research, 2023)
This research reviews and proposes a conceptual framework that could be useful for other researchers to investigate the influence of Islamic Work Ethics (IWE) on the Employees’ Organizational Commitment (EOC). In detail, this research conceptually proposes the framework to tests the possible relationship between three Islamic values which are Teamwork (T), Effort (E), and Honesty (H). Further investigation should be empirically conducted by using the quantitative data. It is suggested that future researchers to use SmartPLS to unlock all predictions as well as to get the overall model fitness of the framework. This research could enrich the literatures pertaining to IWE and the studies of EOC. Instead, it could benefit employers (organizations) as they could improve their employees’ job performances by improving the employees’ commitment to fulfilling their job and responsibilities. Besides, the organizations can apply and instill this IWE in the workplace to achieve the organizations’ goals and objectives. Furthermore, if the proposed framework proves to be reliable, the IWE could be beneficial to the economy as well because high organizational commitment leads to better productivity at work simultaneously encourage employees to be a better citizen of the organization and inspires them to perform better in their respective workplaces.